2000
DOI: 10.1353/rhe.2000.0004
|View full text |Cite
|
Sign up to set email alerts
|

Should I Stay or Should I Go? Student Descriptions of the Doctoral Attrition Process

Abstract: Little is known about the process of doctoral student attrition. Relying on theories of socialization and integration, this paper examines the cases of three students who left their doctoral programs. Their experiences show that academic integration pla ys a greater role in attrition than social integration. Furthermore, the academic integration process can be ruptured, particularly when a student-advisor relationship ends. The paper also questions the idea that degree completion equals success and tha t a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
360
1
14

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(385 citation statements)
references
References 23 publications
10
360
1
14
Order By: Relevance
“…The findings of this study are consistent with themes identified in other studies which deal with doctoral student challenges and also identified new challenges. Various studies in the doctoral education have previously examined the importance of faculty member involvement (Golde, 2000), cultural issues (Lim, Dannels, & Watkins, 2008), support systems (Hoskings & Goldberg, 2005) in helping doctoral student overcome challenges. The existing study found that some of the other challenges such as Absence of human interaction, financial difficulties, course structure and workload also impact online students enrolled in professional doctorate programs.…”
Section: Discussion Implications and Avenues For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study are consistent with themes identified in other studies which deal with doctoral student challenges and also identified new challenges. Various studies in the doctoral education have previously examined the importance of faculty member involvement (Golde, 2000), cultural issues (Lim, Dannels, & Watkins, 2008), support systems (Hoskings & Goldberg, 2005) in helping doctoral student overcome challenges. The existing study found that some of the other challenges such as Absence of human interaction, financial difficulties, course structure and workload also impact online students enrolled in professional doctorate programs.…”
Section: Discussion Implications and Avenues For Future Researchmentioning
confidence: 99%
“…Research indicates that the doctoral students in general and particularly online doctoral students face numerous challenges from a cultural and an academic standpoint and this has been identified as a major cause of student dropout from doctoral programs (Barnett, Basom, Yerkes, & Norris, 2000;Brus, 2006;De Valero, 2001;Di Pierro, 2013;Golde, 2000;Protivnak & Foss, 2009). Students enrolled in the professional doctoral programs face numerous challenges and a systematic investigation in this area is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This necessitates that foci and elements of supervision change during the process as well. First the research theme as well as concepts become specified (Golde, 2000;Rae, 2002). After deciding these fundamental directions, the PhD student can start familiarizing with the theory, methodology, and practice related in the research theme (McWilliam et al, 2005).…”
Section: The Emphases Of Caring Supervision Change During the Processmentioning
confidence: 99%
“…He or she has to evaluate the progress of a thesis in the light of the criteria set by the academic community (see Golde, 2000). A PhD thesis is a research-based, scientific presentation in one of the academic fields.…”
Section: A Caring Supervisor Monitors the Fulfillment Of The Qualitymentioning
confidence: 99%
“…Danışman desteğinin niteliğinin, tez öğrencisinin araştırma beceri ve tutumlarının kabul edilebilir standartlara ulaştırma-da, danışmanın zaman ayırması ve uzmanlık gücünün kilit rol oynadığını (Le ve Seale, 2007); görüşme sıklığı ve niteliğinin ise süreci, dolayısıyla da başarıyı olumlu etkilediği görülmektedir (Golde, 2000;Kam, 1997). Danışmanın dinleme becerileri, cesaretlendirici ve destekleyici tutumu ile bu tutumu gerekçe-lendirme biçimi, tartışmaya açıklığı, yakın, ilgili ve kibar yaklaşımın öğrencileri olumlu etkiliyor (Seagram et al, 1998).…”
Section: Introductionunclassified